In vitro Sequestration of Molecular and Mass Spectra Characterized Metallophilic Cadmium Tolerant Bacteria for Sustainable Agriculture - Uqab, Baba; Nazir, Ruqeya; Ganai, Bashir Ahmad; Rahi, Praveen (Frontiers in Microbiology, 2022)
Due to industrialization, the contamination of toxic metals in soils is currently one of the major concerns to scientists worldwide. The presence of high concentrations of heavy metals including cadmium in the environment is mainly attributed to human activities. Being a highly toxic metal, cadmium can enter plant cell transporters usually used for the uptake of essential cations such as iron, calcium, zinc, etc. This study deals with the appraisement of response and tolerance shown by various bacteria in varied cadmium concentrations (100 ppm to 1000 ppm). The optical density (OD) of the isolates were measured to determine the minimum inhibitory concentration of cadmium (MIC). Isolated bacteria have been identified using 16S rRNA gene sequence and MALDI-TOF MS. Among the 72 isolates, 07 (Pseudomonas putida, Bacillus pumilus, Klebsiella pneumonia, Pseudomonas mandelii, Pseudomonas avellanae, Enterobacter kobei, and Staphylococcus equorum), isolates had efficacy for cadmium tolerance and showed sequestration potential at varying MIC. Furthermore, Klebsiella pneumonia was observed to have the highest (900 ppm) tolerance for cadmium and the lowest (600 ppm) was shown by Enterobacter kobei. Besides, Klebsiella pneumonia showed the highest (75.2%) sequestration potential while the least (52.4 %) was observed for Pseudomonas putida. These cadmium tolerant species can be used as microbial consortia in contaminated environments for detoxification and elimination of cadmium from these agricultural fields.